Effects of Dietary Supplementation with Turmeric and Ginger on Growth Performance and Antioxidant Enzyme Status in Pig - Bhargav, Kakumanu; Reddy, Lingamdinne Siva Sankar Varaprasad; Naik, Bonath Rambabu; Sivakumar, Avadhanam Venkata Naga; Chakravarthi, Matha Kalyana (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
This research was aimed to evaluate the effect of dietary supplementation of turmeric and ginger @ 1% on the body weight on antioxidant profile in SVVU T-17 grower pigs. The study conducted over 60 days evaluated 72 SVVU T-17 crossbred grower pigs, which were divided into three groups. C (Control) group received only basal diet (as per NRC, 2012); T group supplemented with Turmeric @ 1% in basal diet and G group supplemented with Ginger @ 1% in basal diet. Results demonstrated that the treatment group T (42.33±0.91 kg) exhibited significantly higher mean body weights (p<0.05) compared to the control C (36.66±1.08 kg) and G group (36.00±2.55 kg). Antioxidant enzymes SOD (Superoxide Dismutase), Catalase and GSH-Px (Glutathione peroxidase) levels also increased significantly (p<0.05) in the treatment groups compared to the control. Additionally, lipid peroxidation levels (concentration of MDA) were decreased significantly (p<0.05) in Turmeric and Ginger supplemented groups compared to the control. These findings suggest a potential association between these antioxidant enzyme levels and the body weight gain of pigs, and that the dietary supplementation with Turmeric and Ginger significantly improves the antioxidant enzymes by decreasing lipid peroxidation levels and thereby improving the body weight gain in pigs.